Comorbidity and multimorbidity in patients with cirrhosis, hospitalised in an internal medicine ward: a monocentric, cross-sectional study - Lenti, Marco Vincenzo; Ballesio, Alessia; Croce, Gabriele; Brera, Alice Silvia; Padovini, Lucia; Bertolino, Giampiera; Di Sabatino, Antonio; Klersy, Catherine; Corazza, Gino Roberto (BMJ open, 2024)
ObjectivesThere are no data regarding the prevalence of comorbidity (ie, additional conditions in reference to an index disease) and multimorbidity (ie, co-occurrence of multiple diseases in which no one holds priority) in patients with liver cirrhosis. We sought to determine the rate and differences between comorbidity and multimorbidity depending on the aetiology of cirrhosis.DesignThis is a subanalysis of the San MAtteo Complexity (SMAC) study. We have analysed demographic, clinical characteristics and rate of comorbidity/multimorbidity of patients with liver cirrhosis depending on the aetiology—alcoholic, infectious and non-alcoholic fatty liver disease (NAFLD). A multivariable analysis for factors associated with multimorbidity was fitted.SettingSingle-centre, cross-sectional study conducted in a tertiary referral, academic, internal medicine ward in northern Italy (November 2017–November 2019).ParticipantsData from 1433 patients previously enrolled in the SMAC study were assessed; only those with liver cirrhosis were eventually included.ResultsOf the 1433 patients, 172 (median age 79 years, IQR 67–84; 83 females) had liver cirrhosis. Patients with cirrhosis displayed higher median Cumulative Illness Rating Scale (CIRS) comorbidity (4, IQR 3–5; p=0.01) and severity (1.85, IQR 16.–2.0; p<0.001) indexes and lower educational level (103, 59.9%; p=0.003). Patients with alcohol cirrhosis were significantly younger (median 65 years, IQR 56–79) than patients with cirrhosis of other aetiologies (p<0.001) and more commonly males (25, 75.8%). Comorbidity was more prevalent in patients with alcohol cirrhosis (13, 39.4%) and multimorbidity was more prevalent in viral (64, 81.0%) and NAFLD (52, 86.7%) cirrhosis (p=0.015). In a multivariable model for factors associated with multimorbidity, a CIRS comorbidity index >3 (OR 2.81, 95% CI 1.14 to 6.93, p=0.024) and admission related to cirrhosis (OR 0.19, 95% CI 0.07 to 0.54, p=0.002) were the only significant associations.ConclusionsComorbidity is more common in alcohol cirrhosis compared with other aetiologies in a hospital, internal medicine setting.